Ant communities and their trophobionts shape the incidence of pests and diseases in Indonesia’s coffee agroforestry system - FAIZ NASHIRUDDIN MUHAMMAD; AKHMAD RIZALI; BAMBANG TRI RAHARDJO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Muhammad FN, Rizali A, Rahardjo BT. 2024. Ant communities and their trophobionts shape the incidence of pests and diseases in Indonesia’s coffee agroforestry system. Biodiversitas 25: 1127-1134. Ants play various roles in a coffee agroecosystem, and their presence may impact biological control in coffee plantations. Despite the pantropical economic importance of coffee, most research is focused on the Americas. This study investigates how ant communities and their trophobionts shape the incidences of pests and diseases in the Indonesian shade coffee agroecosystem. Three 30 m x 30 m plots consisting of a total of 256 coffee plants were observed from January to March 2022. Ant communities and their trophobiont were observed using three methods: visual, tuna bait, and live bait. The ants found were classified into dominant and non-dominant based on their nesting behavior and dominance in the bait trap. Pest damage and disease intensity observation were also conducted three times. Generalized linear models were used to test the relationships between ant, hemipteran, coffee berry borer, twig borer damage and leaf rust disease intensity. Twenty-one species of ants were found, and five of them were categorized as dominant ants. Ants correlate coffee pest damage and disease intensity, their hemipteran trophobionts, or both. Dolichoderus thoracicus ant positively correlated with all trophobiont hemipteran and negatively correlated with twig borer damage. Technomyrmex albipes positively correlated with aphids but negatively with flatids. Meanwhile, Tetraponera sp.1 ant only positively correlated with flatids. In trophobiont hemipteran group, all except aphids positively correlated with coffee pests and disease. Scale insect Coccus viridis positively correlated with coffee leaf rust and twig borer infestation intensity, while flatid presence even positively correlated with all coffee plant pest and disease intensity. Indirectly, ants may reduce coffee pests and diseases through hemipteran suppression. The results suggest that the interaction of ants and their trophobiont hemipteran can act as a biological control agent for coffee pests and diseases.